Enhancing Vocational Students’ Creativity via Virtual Project Based Automotive Paint Mixing in Teacher Professional Education Program (PPG) Partner School - Irawan, Dani; Kurniawan, Citra; Suhartadi, Syarif; Mindarta, Erwin Komara (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Vocational education in Indonesia faces significant challenges in providing practical learning that is safe, contextual, and aligned with the demands of Industry 4.0. In automotive bodywork painting, vocational students often face constraints such as limited practice facilities, exposure to hazardous chemicals, and restricted opportunities for creative exploration. This study addresses those challenges by developing and implementing a Virtual Project-Based Learning (VPjBL) model at SMK PGRI 3 Malang, a partner school of the Teacher Professional Education (PPG) Program at Universitas Negeri Malang. Using a Design and Development Research (DDR) approach, the study involved three main stages: (1) development of a VPjBL model using the V-MIX AutoPaint simulation software, (2) validation by vocational education experts and industry practitioners, and (3) limited implementation at the partner school. A total of 36 students from the Automotive Body Engineering program participated. Data were collected using creativity pretests and posttests, observations, and interviews. Quantitative data were analyzed using N-Gain scores, while qualitative data were analyzed thematically. Results showed moderate improvement in all creativity dimensions.—with an average N-Gain score of 0.52. The VPjBL model enabled digital-based creative exploration, improved students’ digital literacy, and fostered collaborative skills. Theoretically, these findings provide empirical evidence that integrating VR-supported and project-based learning approaches can enhance creativity, digital competence, and engagement in vocational education. Practically, the VPjBL model offers an innovative framework for schools and teachers to implement safe, interactive, and future-oriented automotive learning aligned with Industry 4.0 and electric vehicle technology development.